2016
DOI: 10.1093/ehjci/jew049
|View full text |Cite
|
Sign up to set email alerts
|

Relative clinical and economic impact of exercise echocardiography vs. exercise electrocardiography, as first line investigation in patients without known coronary artery disease and new stable angina: a randomized prospective study

Abstract: In this first randomized study, ESE was more efficacious and demonstrated superior cost-saving, compared with ExECG when used as the initial investigation for the evaluation of CAD in patients with new-onset suspected SA without known CAD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
1
8

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(26 citation statements)
references
References 20 publications
1
16
1
8
Order By: Relevance
“…Data regarding the prognostic significance of abnormal stress echocardiography has been well demonstrated in several studies. (6)(7)(8)(9)(10)(11)(12) Our study also consistently demonstrated that patients with positive stress echocardiography, regardless of stress ECG findings, will have a higher risk of developing MACE (OR 20.78, p < 0.001). Of note, patients with more than one of the following comorbidities, such as hypertension, hyperlipidaemia or diabetes mellitus (OR 3.69, p = 0.024), were at a higher risk of developing MACE.…”
Section: Discussionsupporting
confidence: 75%
“…Data regarding the prognostic significance of abnormal stress echocardiography has been well demonstrated in several studies. (6)(7)(8)(9)(10)(11)(12) Our study also consistently demonstrated that patients with positive stress echocardiography, regardless of stress ECG findings, will have a higher risk of developing MACE (OR 20.78, p < 0.001). Of note, patients with more than one of the following comorbidities, such as hypertension, hyperlipidaemia or diabetes mellitus (OR 3.69, p = 0.024), were at a higher risk of developing MACE.…”
Section: Discussionsupporting
confidence: 75%
“…Current clinical practice and appropriateness guidelines recommend either exercise treadmill testing (ETT) or non-invasive cardiac imaging tests—such as stress echocardiography (SE), myocardial perfusion scintigraphy (MPS) and coronary computed tomographic angiography (CCTA)—to diagnose, prognosticate risk and impact therapeutic decision making for patients with an intermediate pre-test likelihood of stable CAD(26). Non-invasive cardiac testing with imaging has been favored by some as an initial test for symptomatic patients with at least intermediate pre-test likelihood of obstructive CAD, given its superior ability to diagnose CAD, reclassify CAD likelihood, predict CAD events, and guide subsequent treatment over testing without imaging(3, 7–9). Accordingly, rates of performance of noninvasive cardiac imaging tests have exploded, with growth in imaging outpacing that of other physicians services by more than a factor of two(10).…”
Section: Introductionmentioning
confidence: 99%
“…Despite the high utilization and numerous options for noninvasive cardiac testing, uncertainty remains regarding the optimal testing strategies(12, 13). Multiple studies have investigated the value of ETT in comparison with non-invasive imaging modalities, however, a direct comparison of varying diagnostic strategies that employ non-invasive tests in isolation versus in succession to one another has to date not been assessed(9, 13). Further, the opportunity costs of testing strategies that begin with ETT as compared to that that begin with imaging have not been fully evaluated(13).…”
Section: Introductionmentioning
confidence: 99%
“…Использование МКСЭ у пациентов с плохим качеством визуалиации отражается и на экономической стороне вопроса, так как стоимость самого контрастного препарата более чем компенсируется экономией, полученной за счет сокращения повторных исследований и более низкой частоты ложноположительных и ложноотрицательных результатов [13]. В частности, по сравнению с нагрузочной ЭКГ и однофотонной эмиссионной компьютерной томографией (ОЭКТ) МКСЭ реже требует проведения дополнительных уточняющих методов исследования, что коррелирует со значительно меньшими экономическими затратами [14].…”
Section: оценка региональной сократимости миокардаunclassified